High and low levels of organizational adaptation: An empirical analysis of strategy, structure, and performance - Jennings, Daniel F.; Seaman, Samuel L. (Strategic Management Journal, 1994)
Abstract In this study, we have examined high and low levels of organizational adaptation to environmental change by analyzing strategy, structure, and performance relationships. Our results indicate that organizations with particular levels of adaptation tend to have specific strategy‐structure arrangements which yield certain performance results. Organizations with an optimum strategy‐structure match tend to have higher performances. Implications for future research in organizational adaptation are discussed.